Productivity of maize (Zea mays L.) as affected by varieties and sowing dates - Dil Bahadur Gurung; Balram Bhandari; Jiban Shrestha; Mahendra Prasad Tripathi (Hasanuddin University, 2018)
Genotypic yield potential of maize varieties is greatly affected by sowing dates. In order to investigate the effects of sowing dates and varieties on the grain yield of maize, the field experiment was carried out at research field of National Maize Research Program (NMRP), Rampur, Chitwan, Nepal from April 2009 to March 2010. Three varieties namely Rampur Composite, Arun-2 and Gaurav were sown at every week. The results of experiment showed that interaction effect of variety and sowing date on grain yield of maize was significant. Rampur Composite produced highest grain yield (6.1 t/ha) in August and lowest yield (2.6 t/ha) in May. Similarly Arun-2 produced highest yield (4.6 t/ha) in August and lowest yield (2.1 t/ha) in May. Gaurav produced highest grain yield (5.1 t/ha) in September followed by 4.9, 4.8 and 4.6 t/ha in February, July and August respectively and lowest yield (1.5 t/ha) in November. The sowing date was highly significant on grain production. The highest grain production was 5.1 t/ha in August followed by in February (4.9 t/ha), September (4.6 t/ha) and March (4.4 t/ha) respectively. The lowest grain yield was produced in May (2.4 t/ha). Therefore it was concluded that August planting was best for higher grain production of maize varieties (Rampur Composite, Arun-2 and Gaurav) in terai region of Nepal.